Antiviral Treatment for Hepatitis C Virus Infection after Liver Transplantation - Sugawara, Yasuhiko (Hindawi Publishing Corporation, 2010)
A significant proportion of patients with chronic hepatitis C virus (HCV) infection develop liver cirrhosis and complications of end-stage liver disease over two to three decades and require liver transplantation, however, reinfection is common and leads to further adverse events under immunosuppression. Pretransplant antiviral or preemptive therapy is limited to mildly decompensated patients due to poor tolerance. The mainstay of management represents directed antiviral therapy after evidence of recurrence of chronic hepatitis C. Combined pegylated interferon and ribavirin therapy is the current standard treatment with sustained viral response rates of 25% to 45%. The rate is lower than that in the immunocompetent population, partly due to the high prevalence of intolerability. To date, there is no general consensus regarding the antiviral treatment modality, timing, or dosing for HCV in patients with advanced liver disease and after liver transplantation. New anti-HCV drugs to delay disease progression or to enhance viral clearance are necessary.